Geochemistry of silicate melt inclusions in middle and southern Okinawa Trough rocks: Implications for petrogenesis and variable subducted sediment component injection. (4th May 2018) - Li, Xiaohui; Zeng, Zhigang; Yang, Huixin; Yin, Xuebo; Wang, Xiaoyuan; Chen, Shuai; Ma, Yao; Guo, Kun
Abstract : Silicate melt inclusions (SMIs) in olivine, clinopyroxene, and orthopyroxene in basalt and trachyandesite of the middle Okinawa Trough (MOT) and in basaltic andesites of the southern Okinawa Trough (SOT) were investigated in detail to understand the evolution of magma and geochemical characteristics of the basaltic magma source. Both the SMIs and host bulk rocks are more heavily enriched with Pb and large ion lithophile elements than with high field strength elements and rare earth elements. The major element compositions of SMIs in the MOT trachyandesite show a scattered variation trend of medium‐K to shoshonitic series and suggest that a K‐rich magma source may exist in the Okinawa Trough. Two groups with distinct element distribution patterns observed in SMIs of the MOT trachyandesite may represent magmas with different evolutionary histories. Compared with fractional crystallization and partial melting processes, magma mixing may serve as a reasonable process for the production of trachyandesite in the MOT. Fractional crystallization has played an important role in basaltic magma evolution in the MOT and SOT. Simulations conducted using MELTS show that the fractional crystallization evolution trends observed correspond well to the presence of a magma chamber at 300 MPa with an H2 O content level of 0.2 wt% in the MOT and to the presence of a magma chamber at 300 MPa with an H2 O content level of 0.4 wt% in the SOT. Ratios of incompatible trace elements (e.g., Th/Ce, Th/Sm, Ba/Th, and Th/Nb); positive Pb anomalies; negative Nb, Ta, and Ti anomalies; and the existence of organic hydrocarbons (Cn Hm ) in the SMIs can be attributed to the involvement of subducted sediment from the subducting slab. Modelling results suggest that more primitive magma represented by SMIs from the MOT has formed through the melting of less than 6% of a metasomatized depleted mantle with contributions of 1.2% sediment melt and 0.8% sediment fluid. In contrast, more primitive magma from the SOT formed through the melting of 4–10% of the depleted mantle with contributions of 3% sediment melt and 1% sediment fluid. The different features of the SMIs together with different tectonic settings of the MOT and SOT have formed in response to the westward subduction of the Philippine Sea Plate.